The application of the Canvas business model and its influence on the business productivity of olive companies in the district La Yarada Los Palos, year 2019 - Portugal Mamani, Evelyn Massiel (2021)
The objective of the research was to determine the influence of the Canvas business model on the Business Productivity of the olive companies of the La Yarada Los Palos District, in 2019. The methodology used consisted of a correlational analytical design, we worked with two olive companies in the sector called Sur Oliva S.A.C. and Baumann Crosby S.A. Where the Canvas business model was evaluated from two perspectives; Canvas and the questionnaire of 13 questions applied to 20 workers and customers, business productivity was evaluated with a questionnaire of 9 questions using the Likert scale to 20 workers and customers of the units of study. The results of the companies under study from the nine elements of the Canvas model were; Key resources, Activities, Key alliances. Also the Value Proposition. In addition, the type of market segment, customer relationships, distribution channels. Finally, the costs (in production and processing) and the sources of income were established. The statistic used to test the hypothesis was the Chi-square at 95% reliability where it was significant so that business productivity is influenced by the Canvas business model.